Maximising the relevance and dissemination of the IOC medical consensus statements: a knowledge management perspective - Fortington, L.; Morgan, A.; Sibson, R.; Badenhorst, M.; Emery, C.; Derman, W.; Pasanen, K.; Verhagen, E.; Schwellnus, M.; Finch, C. (British Journal of Sports Medicine, 2021)
Background There have been 27 consensus statements published under the International Olympic Committee (IOC) Medical and Scientific Commission with a goal of contributing to the mission of injury prevention and protection of athlete health. The success of these statements in achieving this goal has not been evaluated. Knowledge management (KM) considers the identification, acquisition, creation and storage, transfer and application knowledge. The KM process of transforming knowledge into relevant and shareable information is important to consider, to ensure the statements are adaptable and useable to local contexts in sports medicine.